Spatial apportionment of urban greenhouse gas emission inventory and its implications for urban planning: A case study of Xiamen, China. (February 2018) - Zhang, Guoqin; Ge, Rubing; Lin, Tao; Ye, Hong; Li, Xinhu; Huang, Ning
Graphical abstract: Highlights: A spatial apportionment framework of GHG emission inventory was proposed. Case study showed ranking of carbon emission intensity for different land-use types. Most land-use types in the central region of case study city had high GHG emissions. Implication for planning is discussed in terms of structure and connection strategies. Abstract: Cities have become a major source of greenhouse gas (GHG) emissions and controlling urban GHG emissions is a critical response to global climate change. Many previous studies on urban GHG emissions focused on inventories, changes and impact factors but few investigated the distribution of spatial sources within a city. Although inventories of a city can give information of GHG emissions from different sectors, urban government and planners need to know where emissions occur and how (or why) they occur where they do. It is thus important to spatially apportion GHG emission within a city for the practical application of GHG emission management and policies. In this study, we develop a framework for the spatial apportionment of urban GHG emissions. Xiamen is taken as a typical rapidly urbanizing city in China to demonstrate the framework of spatial apportionment. Results show that the ranking of GHG emission intensity for different land-use types of the city is manufacturing, mining, warehouse land, service industry land, transportation land, residential land and agriculture land with a ratio of 89:54:23:14:1. The vast majority of land for GHG sequestration was located in the peripheral area of the city and most land-use types in the central region of Xiamen had high GHG emissions. The implication for low-carbon urban planning is then discussed in terms of structure and connection strategies. Integrated with socioeconomic factors and urban land-use distribution, the spatial apportionment of GHG emission inventory can provide a more accurate analysis of emission sources and better management of emission sources through urban planning.